Legal Analysis of Anti-Dumping Cases Raised against Saudi Arabias Petrochemical Products (Global Journal of Human-Social Science, 2014)
The subject matter of this article is to examine some of the anti-dumping cases against the Saudi Arabian petrochemical products by the European Union (EU), Turkey and India. The repetition of having anti-dumping cases against these products has raised a question about the reasons behind this scenario as well as the impact of such cases on these products and the whole Saudi Arabian petrochemical sector. There is a strong link between having cheap raw materials in this sector and anti-dumping cases, since Saudi Arabia is one of the largest oil producer and reserve in the world. Moreover, Saudi Arabia needs to establish a realistic and practicable competition polices inside its market in the context of these products. Yet, Saudi Arabian government still owns the majority of the petrochemicals industries, which makes these products target for the anti-dumping cases abroad.
Keywords: anti-dumping cases; WTO agreement; petrochemical products and saudi arabian law